The Potential of Blockchain Technology for Collaboration among Countries - Bicca Charczuk, Jefferson; Silva, Kerley; da Silva Lima, Marco Tulio (Conference on Digital Government Research, 2025)
In today’s interconnected world, cooperation between countries is crucial, whether to deal with challenges or opportunities in the economic, social, technological or environmental perspective. This document proposes a workshop regarding the potential use of blockchain technology to foster international cooperation among different countries, to address opportunities and challenges. Cross-border collaboration is often hindered by inefficiencies, lack of transparency, and trust issues between nations. Blockchain technology, characterized by its decentralized, transparent, and immutable nature, has the potential to change the way countries collaborate, offering new opportunities for more efficient, secure, and trusted cooperation.